A Novel Integrated Power Detection Circuit for Low Noise Amplifiers in Cellular Applications - Spielberger, Alexander; Scheller, Kai; Engelmann, Andre; Franchi, Norman; Weigel, Robert; Pfannenmüller, Christof (IEEE Wireless and Microwave Technology Conference (WAMICON) 2025, 2025)
A novel power sensing method, integrated in low noise amplifier architectures is presented and demonstrated in 130 nm SiGe BiCMOS technology. The power sensor architecture can be utilized to detect blocking signals by supply current varia- tions caused from different amplifier saturation states. Therefore the combined amplifier/power sensor architecture overcomes the need of additional components in the RF signal path for input power sensing. Two sensor architectures are compared while one is implemented. The architectures ability to indicate input power by amplifier saturation is proven by measurement. It is shown that the sensor gives direct feedback at early stages before the amplifier is in full saturation. The amplifier achieves a maximum gain of 14.31 dB and is optimized for the 5G low-band frequency range from 600 MHz to 1 GH
Keywords: Low-noise amplifier; integrated power sensor; mobile communication; Cellular technology; 5G; 4G

A Novel Neuropredictive SAR ADC Architecture for Ultra-Low Power Applications - Spielberger, Alexander; Pfannenmüller, Christof; Spitzkopf, Lucas; Armbrecht, Wolfgang; Schrotz, Albert-Marcel; Weigel, Robert; Franchi, Norman (68th IEEE International Midwest Symposium on Circuits and Systems, 2025)
This paper proposes a new type of neuromophic analog to digital converter, the neuropredictive SAR ADC. By estimation of the next input value using a neuromorphic predictor, the conversion time of a modified SAR ADC and thus the energy consumption of the ADC can be reduced. A demonstrator designed for audio signals shows an energy saving of 41.09% compared to conventional SAR sampling. This ADC architecture is an alternative for ultra-low power application
https://cris.fau.de/converis/publicweb/Publication/342443079
Keywords: neuromorphic adc; neuropredictive SAR; SAR; ultra-low power

Resistive Matching Techniques in Electrical Balanced Duplexer Systems - Spielberger, Alexander; Pfannenmüller, Christof; Weigel, Robert; Fischer, Georg (Asia-Pacific Microwave Conference 2024, 2024)
Electrical Tunable Duplexers allow multi-use of RF front ends. A broadband impedance tuner is required for high isolation. This paper deals with how the use of a Digital Tunable Resistor (DTR) can improve the tuning range of such a tuner. In the following a possible DTR realization is shown, which converts a linear control voltage into a linear relation of the reflection coefficient. This can be used to map a reflection coefficient of -0.9 to 1 up to a frequency of 6 GHz. <br
Keywords: electrical balanced duplexer; mobile communication; resistive matching; digital tunable resistor